(untitled) (CIPEEX, 2026)
Introduction: Spirituality is an important resource for promoting mental health, especially among healthcare students, who face high levels of stress, anxiety, and academic overload. Objective: To interpret the academic reality of students enrolled in the Nursing program at the Evangelical University of Goiás - Anápolis Campus regarding their mental health and determine the influence of spirituality on this perspective. Method: This is a descriptive, cross-sectional, qualitative study conducted with 100 nursing students from UniEvangélica. Scales were applied to assess spirituality, mental health, and socioeconomic profile. Data were analyzed in SPSS 16.0 using descriptive statistics and correlation tests, considering p<0.05. Results: Spirituality had a protective effect against stressors linked to the academic environment. Negative correlations between spirituality and psychological symptoms showed that students with higher scores on the SSRS, WHOQOL-SRPB, and FACIT-Sp scales had lower levels of depression, anxiety, and stress. Conclusion: The findings reinforced the need to consider the spiritual dimension as a positive aspect of students’ mental health, acting as a resilience factor in the face of academic demands.